Hipertensi Melalui Terapi Aktivitas Berjalan Kaki Dengan Pendekatan Keperawatan Keluarga - Edy Bayudianto; Kipa Jundapri; Suharto Suharto (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2022)
Background: Walking exercise is an exercise for hypertension patients which is useful for stabilizing the blood pressure of patients’ hypertension. Objective: walking exercise is expected to reduce the risk of complications due to increased blood pressure in patients’ hypertension. Methods: This research is a case study research with a family nursing care approach. The study was conducted by two hypertension patients who were given educational intervention and observation of walking exercises to stabilize blood pressure. Results: The study showed that there was a decrease in blood pressure in patients’ hypertension after a walking exercise intervention. In patient I, the blood pressure before the intervention was 160/90 mmHg, and after the intervention became 140 mmHg, while in patient II, the blood pressure before the intervention was 160/100 mmHg and after the intervention was 140/90 mmHg. Conclusion: Walking exercise can stabilize blood pressure and is safe to do in patients, so walking exercise is recommended for hypertension sufferers. The research recommendation is that walking exercise can be applied to patients’ hypertension so that blood pressure becomes stable. Keyword: Hypertension, walking exercise, blood presure